Galvanic corrosion of AZ31B joined to dual-phase steel with and without Zn layer by ultrasonic and friction stir welding - Jiheon Jun; Vineet V. Joshi; Alasdair Crawford; Vilayanur Viswanathan; Donovan N. Leonard; Jian Chen; Piyush Updadhyay; Yong Chae Lim; Zhili Feng (Journal of Magnesium and Alloys, 2023)
Galvanic corrosion of AZ31B joined with bare or Zn-coated DP590 steel by ultrasonic spot welding or linear friction stir welding was quantitatively studied by pre-defining anode and cathode in the lap joint samples. Corrosion volume and depth from Mg anode surfaces exposed to 0.1 M sodium chloride solution was analyzed as functions of cathode surface type and welding method. Characterization of as-welded joints was performed to identify any microstructural feature of the bonding zone that could impact galvanic corrosion behavior. COMSOL modeling with modified user subroutine was conducted to simulate the progression of Mg corrosion in the same joint and electrode configurations used for the corrosion experiments. The experimental results indicated that Zn-coated cathode surface can reduce Mg galvanic corrosion significantly as galvanic polarization and cathodic current on Zn-coated surface remained relatively low for Mg in the weld joints. COMSOL modeling described the growth of Mg galvanic corrosion in a reasonable manner but showed limitation by underestimating the corrosion volume as it did not capture self-corrosion.